Atom probe tomography for advanced nanoelectronic devices: Current status and perspectives. (15th April 2018) - Barnes, J.P.; Grenier, A.; Mouton, I.; Barraud, S.; Audoit, G.; Bogdanowicz, J.; Fleischmann, C.; Melkonyan, D.; Vandervorst, W.; Duguay, S.; Rolland, N.; Vurpillot, F.; et al.
Abstract: Atom probe tomography is unique in its ability to image in 3D at the atomic scale and measure composition in a semiconductor device with high sensitivity. However it suffers from many artefacts. The current state of the art of nanoelectronic device analysis by atom probe is addressed and the challenges in device analysis in the next ten years are laid out. Finally the improvements necessary in sample preparation, instrumentation and reconstruction procedures are discussed. Graphical abstract: